Customer Retention in E-Payments: Identifying the Key Determinants - Pradhan, Silvana; Shrestha, Yeshaswi; Gurung, Pema Dharpo; Munikar, Suyog (New Perspective: Journal of Business and Economics, 2025)
This study examines how key factors such as Customer Trust, Customer Service, Ease of Use, Transaction Transparency, and Perceived Security influence Customer Retention in digital payment systems in Nepal. Furthermore, the study examines the difference in users’ perceived security across different genders. Moreover, the study seeks to examine whether perceived ease of use is associated with age groups and whether there is an association between the frequency of use and customer retention in digital payment systems. A quantitative research method was employed, with a sample size of 250 respondents from and near the Kathmandu Valley. The collected data were coded in SPSS for descriptive and inferential analysis, using Regression Analysis, Independent Sample t-tests, and chi-square tests to assess the relationship between the variables. The findings found that customer retention was significantly influenced by ease of use, transaction transparency, and perceived security. In contrast, customer trust and customer service do not show a statistically significant impact. Furthermore, there was no difference in perceived security across different genders. There is a significant association between age group and perceived ease of use. Moreover, there is a significant association between the frequency of use and customer retention in digital payment systems.